Losses in fishery ecosystem services of the Dnipro river Delta and the Kakhovske reservoir area caused by military actions in Ukraine - Novitskyi, Roman; Hapich, Hennadii; Maksymenko, Maksym; Kutishchev, Pavlo; Gasso, Viktor (Frontiers in Environmental Science, 2024)
We studied the development of commercial and recreational fishing on the Kakhovske Reservoir (aka Kakhovka) and the Dnipro (aka Dnieper) River lowlands in 2020–2023. The fish assemblage of the Kakhovske Reservoir is under consideration for the period 1956–2021. The dynamics of the fish population transformation, species extinction, and the emergence of new invasive species are given. The losses in Kakhovske Reservoir’s ecosystem services as a result of the Kakhovska Hydroelectric Power Plant’s (HPP) Dam explosion in June 2023 are analyzed. The states and prospects for local recreational and commercial fishing development are assessed. By field research and monitoring observations of the Kakhovske Reservoir and the Dnipro River lowland using the Earth remote sensing data, it was established that two months after the accident, the area of the remained reservoir water surface was ~430 km2 (about 19% of the initial, including the restored Dnipro River bed). The newly formed shallow waterbodies, which do not have a water connection between each other, occupy an area of about 300 km2. These areas continue to dry out, shrink, and become overgrown with vegetation. The draining of the Kakhovske Reservoir caused an ecological disaster for about 40 species and subspecies of fish. The total monetary losses of commercial fishing are about $5.5 million annually. Losses in fishery from the vanishing of spawning grounds are estimated at 20,000 tons of fish resources (~$40 million). The negative consequences of the loss of the Kakhovske Reservoir aquatic ecosystems will affect the socio-economic development of the entire South of Ukraine for a long time. Among the major ecosystem services lost is the cessation of water supply. Ukraine’s priority issues are the post-war rehabilitation of the country, its degraded lands, territories, and water areas, and ensuring water and food security. One of the urgent problems will be the feasibility of reconstruction of the Kakhovska HPP’s Dam and restoration of the Reservoir, renovation of water supply, fishery, navigation, energy, and recreation. Biodiversity is a basis for the efficient and sustainable ecosystem functions that provide many ecosystem services, and it should be considered for the post-war recovery and development of Ukraine.